Revisiting the Implications of RSPO Smallholder Certification Relative to Farm Productivity in Riau, Indonesia - Veriasa, Thomas Oni; Nurrunisa, Margaretha; Fadhli, Nurchalis (Forest and Society, 2024)
Indonesia is the largest global producer of palm oil, and smallholder plantations control 40.5% of the national palm oil area. As an essential part of the global supply chain, including palm oil smallholders in RSPO certification schemes is critical for the global market and for achieving environmental sustainability outcomes. This study was conducted in Riau Province, a major palm oil producing region. First, the study investigated RSPO certification implications through a case study in two oil palm smallholder groups in Pelalawan District and Kuantan Singingi District. Second, we analyze the driving factors of palm oil smallholder productivity at the landscape scale by developing an estimation model (panel data regression) using a data set from years 2012-2021 in 11 districts/cities. The findings across the two smallholder groups show that applying RSPO's principles, criteria, and standards gave group members collective direct social-economic and environmental benefits. Applying RSPO standards contributes to gradually increasing smallholder plantations' Fresh Fruit Bunch productivity by 15-20%. Nevertheless, our model shows implications of RSPO Smallholder certification do not significantly contribute to smallholder productivity improvement at the landscape scale. In contrast, increasing oil palm areas does not guarantee increased smallholder productivity in Riau. Smallholder oil palm area expansion also has the potential for higher deforestation if there is no central and local government control and improvement support from related parties. For this purpose, RSPO smallholder certification should be encouraged to pursue broader positive impacts on social, economic, and environmental dimensions at the landscape level.